“Raja adil Raja disembah Raja zalim Raja disanggah” satu model pembinaan negara bangsa (A fair King is a worshipped ruler; A tyrant King is an argued ruler [Raja adil Raja disembah Raja zalim Raja disanggah]: A nation race building model) - Ahmad Sabri, Ahmad Zaharuddin Sani; Hassan, Hazman; Abu, Roziya (2013)
Leadership monarchical is one oldest system leader ship in the world. The concept of throne, government and Rulers is bonding relationship between institutional network and individuals.It’s symbolizing power, moral nature, character, accountability and the essence of soul of an administrative institution. The system of a constitutional ruler on the other, hand refers to the partnership power between a King and its people.A King conceded as source of reference for the people beside becomes a checking mechanism and equality between legislation executive and judicature democratic institution in a country.The reality, as long as people have faith on the King and respect the institutions of monarchical, this system standard recognition will remain firm. However, in this millennium era, Royal Institutions have changed greatly - as a result of industrial revolution,technological development, changing pattern and economic axis and development information technology and communications.The Institution monarchical now needs to prove their levels of achievement leadership, in fulfilling people's hopes, beside displays a behavior and a personality that is in line with dignity and honors given.